Moderate Islam in Yusuf Qardhawi's Perspective - Zaprulkhan, Zaprulkhan; Iskandi, Iskandi (Faculty of Ushuluddin and Religious Study, Universitas Islam Negeri Raden Intan Lampung, 2022)
In today's contemporary era, we often witness the appearance of a fierce, anarchist face of Islam that instigates various forms of social violence. Whereas the portrait of Islam presented by radical circles is not absolute and the only correct Islamic construction. This is because the religious construction that they present socially to the wider community in their rigid, intolerant, and sometimes anarchic form is only one of the results of their reading of the fundamental Islamic doctrines: the Qur'an and the Sunnah which are multi interpretative. It is at this point that presenting a reading of Islam with a moderate style becomes very significant. One of the contemporary Muslim scientists who has done many readings while presenting a portrait of moderate Islam is Yusuf Qardhawi. In most of his works, Qardhawi presents a moderate Islamic discourse. According to Qardhawi, one of the most fundamental characteristics of Islam is wasathiyah which means moderate. This article seeks to explore the construction and application of Yusuf Qardhawi's moderate Islamic thought with a critical-philosophical approach.